The Method of using violin bow (Hawler Music Band as a Sample) - Kawan Ahmad Elias; Hazhar Ahmed Mustafa (Zanco Journal of Humanity Sciences)
It is a descriptive and analytical research; in this research the researchers show some topics and subjects on the way of using violin bow in Hawler music band. The violin instrument is defined as one of the string instruments with bow and its status and characteristic is different from other instruments in using performance techniques with bow, in the history of Hawler music band, this instrument has had a major and an effective role among the instruments of this band in their artistic work. Therefore, the researcher found this research as a necessary one to study styles and techniques of using bow scientifically in Hawler Music band.